An electrochemical sensing approach for scouting microbial chemolithotrophic metabolisms - Saavedra Olaya, Albert Ulises (2018)
The present study was aimed to test an electrochemical sensing approach for the detection of an active chemolithotrophic metabolism (and therefore the presence of chemolithotrophic microorganisms) by using the corrosion of pyrite by Acidithiobacillus ferrooxidans as a model. Different electrochemical techniques were combined with adhesion studies and scanning electron microscopy (SEM). The experiments were performed in presence or absence of A. ferrooxidans and without or with ferrous iron in the culture medium (0 and 0.5 g L−1, respectively). Electrochemical parameters were in agreement with voltammetric studies and SEM showing that it is possible to distinguish between an abiotically-induced corrosion process (AIC) and a microbiologically-induced corrosion process (MIC). The results show that our approach not only allows the detection of chemolithotrophic activity of A. ferrooxidans but also can characterize the corrosion process. This may have different kind of applications, from those related to biomining to life searching missions in other planetary bodies.